Kedaulatan Negara Dalam Invasi Rusia Ke Ukraina Berdasarkan Hukum Internasional - Muhamad Ali Aqsa Haupea; Josina Augustina Yvonne Wattimena; Arman Anwar (PAMALI: Pattimura Magister Law Review, 2023)
Introduction: Russia's invasion of Ukraine gave rise to mixed opinions in the international community regarding the concept of state sovereignty, both in theory and practice.Purposes of the Research:  The regulation of state sovereignty has experienced a conceptual shift according to international law and Russia's invasion of Ukraine has caused a shift in the concept of state sovereignty in international law.Methods of the Research: The research used is normative juridical, using an analytical perspective research type. The legal materials are primary, secondary and tertiary legal materials. The approaches used are the statutory approach, the conceptual approach and the case approach. The technique for collecting legal materials uses library research which is then analyzed qualitatively to answer the problems being studied.Results of the Research: The research results show that the concept of state sovereignty is experiencing changes and shifts in meaning according to developments over time. The revolutionary changes of the late 18th and 19th centuries gave rise to the concept of sovereignty which included the principle of equality of states and the principle of non-intervention in the internal affairs of other states as one of its important elements. Regarding the causes of Russia's invasion of Ukraine, it was influenced by various factors, including historical, political, economic, security and defense factors, as well as to protect pro-Russian separatist groups who wanted to separate themselves from Ukraine. Russia's invasion of Ukraine did not affect the shift in the concept of sovereignty as currently accepted by the international community in the modern ideology of sovereignty. On a theoretical and practical level, the will of the Russian state has great interests in carrying out actions that threaten peace, or violate peace by launching aggression against Ukraine as a sovereign state. Russia as a party to various international agreements has an obligation to respect international law where state sovereignty and equality between countries are recognized concepts and have become the basis of the international legal system